(untitled) (Research, Society and Development, 2021)
The exponential growth of Internet crime, such as pedophilia, often requires estimating age from the facial images of the individuals involved. The objective of this study was to evaluate the applicability of the photoanthropometric method for estimating age with forensic purposes by means of a systematic review. We searched the databases PUBMED, SCOPUS, The Cochrane Library, Web of Science, LILACS, CAPES and SIGLE, using MeSH and free terms based on PICO strategy (P: population, I: intervention, C: comparison, and O: outcome). We included studies that evaluated images of individuals by photoanthropology to estimate forensic age. Data extraction and methodological quality evaluation were performed (QUADAS-2). Of 2809 articles identified, 37 were initially selected for addressing facial analysis through photoanthropology. After reading in full, 9 studies that used the method for age estimation remained. With a sample from 9 different nationalities, 5 articles had their photoanthropometric markings done manually, while 4 were automated. All studies had age groupings for their determination, and there were no coincidences between them. The method of photoanthropometry was considered effective for age estimation in 5 articles, while 4 reported that more studies are needed to minimize errors. Only 3 studies had low risk of bias because they used an applicable and reliable reference standard. Photoanthropometry has limited applicability in the forensic age estimation, and there is questionable evidence that supports its use due to the risks of bias present in the studies.